Romidepsin: a new therapy for cutaneous T-cell lymphoma and a potential therapy for solid tumors. Issue 7 (July 2010) - Grant, Cliona; Rahman, Fahd; Piekarz, Richard; Peer, Cody; Frye, Robin; Robey, Robert W; Gardner, Erin R; Figg, William D; Bates, Susan E
Romidepsin is a histone deacetylase inhibitor (HDI), approved by the US FDA for the treatment of cutaneous T-cell lymphoma (CTCL). Although various mechanisms have been proposed for the activity of HDIs, including induction of genes controlling cell cycle, acetylation of cytoplasmic proteins and direct induction of apoptosis, the mechanism underlying activity of romidepsin and other HDIs in CTCL is not known. Romidepsin induces long-lasting responses. The side-effect profile is similar to that of other HDIs, causing fatigue, nausea and thrombocytopenia. Management of the CTCL population requires vigilence to prevent infection with skin contaminants, and monitoring of potassium and magnesium, electrolytes found to be low in a large proportion of patients. Electrocardiographic (ECG) changes are common but are not associated with myocardial damage. When molecular end points were evaluated in 61 patients enrolled on a Phase II trial with romidepsin, response was associated with persistence of acetylated histone H3, suggesting that drug exposure is important in effective therapy with romidepsin. Future studies will endeavor to identify combination strategies to increase the efficacy both in resistant CTCL and in solid tumors and to identify biomarkers of response that will allow selection of patients most likely to benefit from the therapy.